2014
DOI: 10.1080/00071668.2014.929637
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chromosome instability in Japanese quail (Coturnix japonica)

Abstract: 1. A study of the incidence of chromosome instability in the Japanese quail as assessed by sister chromatid exchange (SCE) and fragile site identification in chromosomes was conducted in two parent breeds and their F1 and F2 generations. 2. The mean incidence of SCEs was 6.02 ± 0.45 and the frequency of fragile sites was 1.17 ± 0.79. 3. There were moderately negative correlations of 0.51-0.64 between chromosome instability and fertility in the F1 and 0.10-0.23 in the F2. The hatch of fertilised eggs was negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussionsupporting
confidence: 44%
“…However, to a certain extent, they correspond with normal cellular processes (Shaffer 1977;Painter 1980;Wo´jcik et al 2004). Approximately 10 SCEs spontaneously occur during a normal cell cycle in man.…”
Section: Discussionmentioning
confidence: 99%
“…Different frequencies of FS have been observed in buffalo by Albarella et al [66], Di Meo et al [67], Genualdo et al [68] and Kumar et al [69]. Different FS values have also been observed in various breeds of pigs [64,70,71], sheep [64,7274], chickens, and quails [32,75]. The results obtained by these researchers indicate that breed has a major influence on the incidence of FS.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by these researchers indicate that breed has a major influence on the incidence of FS. Wójcik et al [75], in a study on quail, evaluated pure breeds (Japanese quail and Pharaoh Coturnix) as well as crosses of these breeds in the F1 and F2 generations. The authors observed the most chromosome damage in the parent generation, slightly less in the F1 generation (crossbreds) and the least in the F2 generation.…”
Section: Discussionmentioning
confidence: 99%
“…Checkpoints in the cell cycle may monitor these regions and block entry into mitosis before their replication is complete (Durkin & Glover, 2007). Therefore, fragile sites are found in all animal species: pigs, cattle, sheep, chickens, geese, and quail (Albarella et al., 2009; Ali, Abdullah, Babar, Javed, & Nadeem, 2008; Gordon et al., 2007; Rønne, 1995; Wójcik, Andraszek, Smalec, Knaga, & Witkowski, 2014; Wójcik & Smalec, 2012; Wójcik & Szostek, 2019; Wójcik et al., 2018). Unfortunately, there are no publications concerning fragile sites identified in coypus.…”
Section: Discussionmentioning
confidence: 99%